Indonesian migrant live-in care workers in rural Taiwan: Making friendships, kinships, and creating social capital overseas - Guritno, Danur Condro; Aryo, Rakhmundia (Universitas Ahmad Dahlan, 2024)
Taiwan serves as a main destination for Indonesian females seeking work as migrant live-in care workers. However, being a migrant worker requires efforts to face challenges and difficulties overseas to achieve family well-being. One of them is utilizing social capital. Studies on social capital among migrants tend to be unisex, with a limited focus on women as the main actors. Therefore, it is crucial to examine how these women create and utilize their social capital to fulfill their needs. This paper examines the form of social capital of Indonesian migrant live-in care workers (LCWs) in Taiwan, highlighting their unique characteristics, given the specific nature of their job roles. Using a phenomenological approach, the study involves in-depth research and direct data collection. Data analysis follows a structured process including data reduction, display, verification, and conclusion. This essay finds a new structure in social capital and migration by positioning women as the main actors. It shows that LCWs primarily rely on bonding social capital, forming strong, exclusive friendships often based on geographical proximity, characterized by long-distance and close-distance patterns. Participation in social groups such as pengajian does not enhance LCWs' social capital, resulting in weak ties within bridging social capital. Additionally, LCWs tend to develop stronger relations with their employers, enabling them to access various resources through linking social capital, which differs from bonding and bridging social capital. This essay concludes that LCWs in Taiwan predominantly utilize bonding and linking social capital to achieve their migration expectations.